Varicose vein surgery - Frings, N.; Glowacki, P.; Tran, P.; Schäfer, L. (Phlebologie, 2006)
Background: The incidence of deep vein thrombosis (DVT) after varicose vein surgery remains largely unknown because of problems with study design in many of the previous reports. Patients, methods: This was a prospective study of 2805 patients (3756 legs) who had standard varicose vein surgery. The operations were done on inpatients under heparin prophylaxis and under local anaesthesia in a sequential way that reduced the duration of each procedure to less than 45 minutes. Before hospital discharge, and again three months later the deep veins of the legs were investigated using duplex ultrasound imaging by an objective phlebologist to determine the incidence of postoperative DVT exclusively in the femoral and popliteal veins (not in the calf veins). Results: All patients were imaged before discharge and 2961 legs (79%) returned for investigation after three months. In none of these was any DVT detected. One patient presented elsewhere with a femoropopliteal DVT and was anticoagulated. This patient was asymptomatic three and twelve months postoperatively. Conclusion: The strategy of sequential short duration varicose vein surgery done under local anaesthesia as an inpatient might be responsible for the low rate of postoperative DVT (0.03 %) in this study.
Keywords: Varicose vein surgery; deep veinous thrombosis; duplex scan; local anaesthesia